Pelatihan Pemulasaran Jenazah bagi Kelompok PKK Desa Kudubanjar - Sholahuddin, Ahmad; Umardiyah, Fitri; Anam, Khoirul; Khotimah, Khusnul; Hidayatulloh, Faisol (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2025)
A phenomenon that has emerged in society today is that people think they don't need to know how to care for a corpse from start to finish because they already have their own staff. This is a weakness if one day a death occurs at the same time, then the disposal of the body will be delayed due to the lack of a search team. Based on this, the team carried out corpse handling training activities as a form of cadre formation and increasing knowledge and skills in fulfilling religious obligations. The targets of the training were members of PKK (family empowerment community) in Kudubanjar Village. The training consists of providing material and practice for one day. The practices carried out include the process of washing the body, shrouding the body, and intersecting the body. Through this training, PKK women who have never known the procedures for exhuming corpses will understand and be able to practice.